A Latin American Critical Conceptual Model on the Adoption of Open Educational Resources. Issue 1 (13th December 2021) - Rodés, Virginia; Gewerc, Adriana
A conceptual model on OER adoption is presented, as the substantive theoretical synthesis of a Grounded Theory study, whose purpose was to identify which factors influence the adoption of OER among teachers in Latin American universities. Main theoretical-methodological bases are rooted and analised, in comparison with the traditional approach identified in the most recent literature. From a double "emic" perspective on agency and structure, the faculty and the university institution, the resultant conceptual model includes four categories influencing the adoption of OER among professors in Latin American universities: 1) Construction of Teacher Professional Identity; 2) Practices and Transformations in the Curriculum; 3) Creation, Use and Opening of Digital Educational Resources; and 4) Social Representations about Repositories of OER. Properties and dimensions of each category are presented and described. The critical conceptual model may be adopted by researchers from all regions who seek to unveil and decolonise the hidden curriculum of OER.